Attitudes towards family formation in cohabiting and single childless women in their mid- to late thirties. (2nd January 2016) - Birch Petersen, Kathrine; Sylvest, Randi; Nyboe Andersen, Anders; Pinborg, Anja; Westring Hvidman, Helene; Schmidt, Lone
Abstract: This study aimed to explore attitudes towards family formation in single or cohabiting childless women of advanced age. The design comprised semi-structured qualitative interviews of 20 women aged 34–39 years attending the Fertility Assessment and Counselling Clinic, Rigshospitalet, Copenhagen. A sample of 10 single women and 10 cohabiting women was chosen with equal distribution of postgraduate education length. Data were analysed using content analysis following the method of Graneheim and Lundman and consolidated criteria for reporting qualitative research (COREQ). The general attitude towards family formation was characterized by a fear of the consequences of choosing motherhood on one hand, and a 'ticking biological clock' and a wish to establish a nuclear family on the other. The women idealized the perception of perfect mothering in terms of uncompromising expectations of child rearing and showed an increasing awareness of solo motherhood as a possible solution to advanced age, the wish of a child and single status compared to earlier studies. Our study contributes to knowledge and understanding of personal considerations related to childbearing in nullipara women in their mid- to late 30s and may be useful in a fertility assessment and counselling setting.